HUBUNGAN USIA MEARCHE IBU DAN KETERPAPARAN MEDIA MASSA DENGAN USIA MENARCHE PADA SISWI SMP NEGERI 1 SALAHUTU - Mariene Wiwin Dolang (Stikes Graha Edukasi Makassar, 2018)
Objective: The purpose of this study was to analyze the relationship between maternal menarche age and exposure to mass media with menarche age in students of Salahutu 1 Junior Hight School. Methods: The research design used in this study was analytic observational with a cross sectional study approach. The population is all students of SMP Negeri 1 Salahutu Class VII and Class VIII in the academic year 2016-2017 using the total sampling technique. The sample in this study amounted to 48 female students. Results: The results showed that there was a relationship between the age of maternal menarche (p = 0,000) and exposure to mass media (p = 0,001) with the age of menarche in the students of Salahutu 1 Middle School. Discussion: Menarche is the first menstrual period at puberty. The age of menarche that occurs too early will have a detrimental effect on health, including children who are quick to get to know their sex lives and quickly feel attracted to the opposite sex. Conclusion: The conclusion in this study is that there is a relationship between the age of maternal menarche and the exposure of mass media to the age of menarche in students of Salahutu 1 Middle School. It is recommended to the school to educate reproductive problems, especially early menstruation, along with the acceleration of the age of menarche in young women